Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-10T21:21:53+02:00
Q(x)=x⁴- 8x³+22x²-24x+9
P(x)=2x³-9x²+7x+6

Q(x)-2P(x)=(x⁴- 8x³+22x²-24x+9)-2(2x³-9x²+7x+6)=
x⁴- 8x³+22x²-24x+9-4x³+18x²-14x-12=x⁴-12x³+40x²-38x-3

W(x)=x^4+(m-4)x³-(2n+6)x²-38x-3

Q(x)-2P(x)=W(x)

x⁴-12x³+40x²-38x-3=x⁴+(m-4)x³-(2n+6)x²-38x-3

Zatem
m-4=-12 więc m=-12+4, zatem m=-8
-(2n+6)=40, -2n-6=40, więc -2n=40+6, -2n=46 /:(-2), n=-23

Odp. Dla m=-8 i n=-23 wielomian W(x) jest równy wielomianowi Q(x)-2P(x)
2009-10-10T21:25:51+02:00
Q(x)-2P(x)=x⁴- 8x³+22x²-24x+9-2(2x³-9x²+7x+6)=
=x⁴- 8x³+22x²-24x+9-4x³+18x²-14x-12=
=x⁴- 12x³+40x²-38x-3
W(x)=x^4+(m-4)x³-(2n+6)x²-38x-3
gdy rowne to
m-4=-12 oraz -(2n+6)=40
m=-8 oraz -2n=46→ n= -23
2009-10-11T00:03:34+02:00
Q(x) = x⁴-8x³+22x²-24x+9
P(x) = 2x³-9x²+7x+6

Q(x) - 2*P(x) = x⁴-8x³+22x²-24x+9-2*(2x³-9x²+7x+6) = x⁴-8x³+22x²-24x+9-4x³+18x²-14x-12 = x⁴-12x³+40x²-38x-3

W(x) = x⁴+(m-4)x³-(2n+6)x²-38x-3

x⁴+(m-4)x³-(2n+6)x²-38x-3 = x⁴-12x³+40x²-38x-3

m-4=-12
m=-8

-(2n+6)=40
-2n-6=40
-2n=46
n=-23